Characteristics of Biodiesel Produced From Palm Oil via Base Catalyzed Transesterification - Cadence Isis, Tay (2012)
The depletion of petroleum has prompted the global oil industry to look at an alternative source for fuel from renewable energy source, one of which is biodiesel. Biodiesel is a notable alternative to the widely used petroleum-derived diesel fuel since it can be generated by domestic natural resources such as palm oil, soybeans, rapeseeds, coconuts and even recycled cooking oil, and thus reduces dependence on diminishing petroleum fuel. Interest in biodiesel has been expanding recently due to government incentives and high petroleum prices. The majority of biodiesel today is produced via base-catalyzed transesterification with methanol. In order to find the optimal values of biodiesel yield, it is suggested to find the optimum reaction temperature, reaction time and the methoxide:oil ratio. In this study, the parameters were: reaction temperature of 40, 50, and 60 (°C); reaction time of 40, 50 and 60 (minutes); and methanol to oil ratio of 4:1, 6:1, and 8:1. For every experiment done, raw CPO was treated with magnesium sulphate to remove excess moisture then heated at 50 °C and mixed with methoxide (potassium hydroxide and methanol) according to the considered parameters. The agitation speed was set at 250 rpm. After the transesterification process was completed, the hot mixture was left to settle for at least 12 hours in a separator funnel. As soon as the separation was done, two layers were formed, the lower layer of glycerine and the upper layer of palm oil methyl ester. The product of palm oil methyl ester was washed with 70 °C hot tap water for few times. The final product of biodiesel was transferred to a heated oven at 50 °C to remove excess water. The optimum biodiesel yield from the research was 88 % at methoxide:oil ratio of 6:1, time of 60 minutes and temperature of 60 °C. These parameters were chosen as optimum because it is cost effective regarding time and chemical consumption. According to the result, around 500 mL of biodiesel was produced and homogenised to be used in the physical properties tests. The tests showed the properties of biodiesel produced with density of 876.0 kg/m3, kinematic viscosity of 4.76 mm2/s, cetane number of 62.8, flash point of 170 °C, cloud point at 13°C, pour point at 17 °C and saponification value 206.95 mg/L. The physical properties biodiesel produced showed that the properties are accepted within ASTM D6751 and European Standards.